A taxonomy of myopic stability concepts for hedonic games - Shao Chin Sung; Dinko Dimitrov (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
We present a taxonomy of myopic stability concepts for hedonic games in terms of deviations, and discuss the status of the existence problems of stable coalition structures. In particular, we show that contractual strictly core stable coalition structures always exist, and provide sufficient conditions for the existence of contractually Nash stable and weak individually stable coalition structures on the class of separable games.
urn:nbn:de:hbz:361-8192
Keywords: C71; A14; D20; 330; Coalition formation; Hedonic games; Separability; Taxonomy; Koalition; Spieltheorie; Gleichgewichtsstabilität; Theorie